Building a caring HyFlex pedagogy: An example of practice in an initial teacher education program (Journal of Applied Learning and Teaching, 2024)
In our Australian regional communities, equity of participation and parity of access to initial teacher education courses have been a long-standing issue. Developing a caring HyFlex pedagogy that positions interpersonal and collegial relationships as central to the teaching and learning process and addresses the tyranny of distance is core to integrating technology and enhancing interaction to overcome barriers within regional communities. This example of practice provides the perspectives of a tutor and a student to illustrate the role of care and technology in building a student’s learning journey. Pairing pedagogical care with a hybrid and flexible (HyFlex) delivery model presents an opportunity for an innovative regional pedagogy that makes a unique contribution to the established literature about both caring and HyFlex technology implementations.